Living with and Through Artificially Intelligent Virtual Personal Assistants: Subservience, Simultaneity and Surveillance in Late-Capitalist Cairo - Elsayed, Habiba Ahmed (AUC Knowledge Fountain, 2021)
The global technological field has witnessed a computing shift - from focusing on human-device use to focusing on human-device ambient and social interaction. This shift is notably accompanied by a societal one that increases desire and dependency on everyday smart technologies powered by artificial intelligence and machine learning. One of such growing AI-enabled technologies is the virtual personal assistant (VPA). In this project, I draw on my filed-work with my four interlocuters in Cairo with their respective VPAs, Siri and Alexa. In analyzing my experiences and observations, I focus on three main themes: subservience, simultaneity and surveillance. Examining the role of gender, labor, identity, discourse, time and temporality, as well as surveillance is at the heart of this work. Guided by Haraway’s cyborgism, Marxist feminism and arguments brought forth by the post-humanities I first begin by a genealogy of the female automata, followed by dissecting gender’s role in VPA design/interaction, as well as capitalist-digital logic. I then move on to discuss the VPAs’ relationship to other digitalities, such as the calendar and smart home contrivances. Finally, I tie previous arguments and observations to how VPAs may be approached as the eyes and ears of Capitalism.